ПЕРЕДУМОВИ ТА ПЕРСПЕКТИВИ РОЗВИТКУ БАНКІВ ВАРТОСТІ (International Journal of Innovative Technologies in Economy, 2018)
The state of the modern financial market is not homogeneous. Various organizations act on it, such as world, investment, public, retail, social, church, green, folk and development banks; official and unofficial banking organizations; shadow financial system. Mutual assistance banks, rural banks, credit unions, savings and loan funds are institutions formed on the basis of mutual assistance among people. There are also banks operating in the «western» financial tradition and those operating under the laws of Sharia. Value banks are social, ethical, green and public banks without a definite management model that function in the form of joint stock companies, unions and private enterprises. In the article, the ways of formation, organizational structures, historical and religious preconditions of creation and modern tendencies of development of value banks are viewed.